Language Environment and Educational Background of Chinese Parents in Sarawak, Malaysia: ESL or EAL? - Lee, Diana Phooi Yan; Ting, Su Hie (Universiti Kebangsaan Malaysia, 2016)
The study examined the language use of Chinese from different educational backgrounds to determine whether their language environment is that of an ESL (English as a Second Language) or EAL (English as an Additional Language) environment. A questionnaire survey involving 400 Chinese parents was conducted in Kuching, Sarawak, of which 239 were Chinese-educated, 81 English-educated, and 80 Malay-educated. The results show that the English-educated participants operate in an ESL environment, with a large proportion using English with their spouse, children and friends, cherishing English the most, and using it for expressing deep feelings. The Chinese-educated participants, on the other hand, mainly operate in an EAL environment, and Mandarin has both utility and affective value. The Malay-educated participants were divided in their use of Mandarin, Chinese dialects and English, and their emotional attachment to these languages. In both the Chinese- and Malay-educated groups, those who are more proficient in English function in an ESL environment whereas those who are less proficient function in an EAL environment. Since the number of Chinese attending English medium private primary schools is negligible and English is no longer the medium of instruction in public schools, the focus should be on the Chinese-educated Chinese because their number is much larger than the Malay-educated Chinese. Going by this, the results suggest that the English language environment for the Sarawak Chinese community in future would be inclined towards EAL rather than ESL because Mandarin will be their primary language, and Malay will most likely be used for interethnic communication, leaving a smaller role for English.